THE SPECIFICS OF HYPERTENSION PREVALENCE IN TYUMENSKAYA REGION AND ITS TREATMENT EFFICACY AMONG INHABITANTS OF 25-64 YEAR OLD - A. Yu. Efanov; M. A. Storojok; I. F. Sholomov; I. V. Medvedeva; S. V. Shalaev (Кардиоваскулярная терапия и профилактика, 2017)
Aim. To study prevalence of arterial hypertension (AH), mean values of  systolic  (SBP)  and  diastolic  (DBP) levels  of  blood  pressure, awareness of patients on this, antihypertension drugs (AD) intake and treatment  efficacy among inhabitants of Tyumen Region, age 25-64 year old.Material and methods. A cohort of Tyumen Region inhabitants, 25-64 y.o.,  investigated  under  the  framework of multicenter  observational study ESSE-RF. Number of participants  — 1762, of those men 34,4% (n=607), women 65,6% (n=1155), mean age 48,9±11,4 y.o.Results. In Tyumen Region the prevalence of AH was 48,9%, which is 4,9% higher than general  population in ESSE-RF (by 9 regions). The same  high pressure was  found  in general  population  of men  and women, however statistically significantly predominated  in men aged <55 y.o. The prevalence  of AH increased  with age  — from 17,1% in group  25-34  y.o. to 70,6%  in group  55-64  y.o.,  significantly more frequently registered  in rural inhabitants — 58,1% vs 46,8% (р<0,05) and those  with lower educational  level — 57,4% vs 47,9% (p<0,05). The specifics  of Tyumen Region was low level of awareness about having AH. In difference with the general ESSE-RF selection, with this value 73,1%, awareness on their AH in Tyumen Region was 57,6%. Naturally, this value was higher in women — 60,5% vs 50,6% (р=0,03), city inhabitants — 59,3% vs 51,7% (p<0,05) and persons  with middlelevel or higher education  — 58,4% vs 47,9% (p<0,05).  Not high was the portion of those regularly taking AD — 39,5%, of those effectively treated  39,1%.  Women with AH  significantly more  commonly  took AD — 43,9% vs 23,0%, and were doing this more effectively  — 43,2% vs 24,3% (р<0,01). Efficacy of AD was higher among those with higher education  — 44,7% vs 35,9% (р<0,01),  decreased with the age and did not relate  on the type of settlement.  Of the specifics  of Tyumen Region was not high portion of those with AH reached  target values of BP — 15,4% vs 22,7% in general population of ESSE-RF. This value did not have significant differences  depending  on the  age  and  type of settlement, but was significantly higher among women in the age group >35 y.o., citizens, as  rurals. Correlation of effective BP control with educational  level was found only in male population. Among hypertensive males with middle and higher education, BP control was significantly better comparing to AH patients with low educational level. Conclusion. The results determined  the aims of prevention work with AH taking the specifics of this factor prevalence in Tyumen Region.